Depressive-like behavioral response of adult male rhesus monkeys during routine animal husbandry procedure - Hennessy, Michael B.; McCowan, Brenda; Jiang, Jing; Capitanio, John P. (Frontiers in Behavioral Neuroscience, 2014)
Social isolation is a major risk factor for the development of depressive illness; yet, no practical nonhuman primate model is available for studying processes involved in this effect. In a first study, we noted that adult male rhesus monkeys housed individually indoors occasionally exhibited a hunched, depressive-like posture. Therefore, Study 2 investigated the occurrence of a hunched posture by adult males brought from outdoor social groups to indoor individual housing. We also scored two other behaviors—lying on the substrate and day time sleeping—that convey an impression of depression. During the first week of observation following individual housing, 18 of 26 adult males exhibited the hunched posture and 21 of 26 displayed at least one depressive-like behavior. Over 2 weeks, 23 of 26 males showed depressive-like behavior during a total of only 20 min observation. Further, the behavior during the first week was positively related to the level of initial response to a maternal separation procedure experienced in infancy. In Study 3, more than half of 23 adult males of a new sample displayed depressive-like behavior during 10 min of observation each of Weeks 7 to 14 of individual housing. The surprisingly high frequency of depressive-like behavior in Studies 2 and 3 may have been due to recording behavior via camera with no human in the room to elicit competing responses. These results suggest that a common animal husbandry procedure might provide a practical means for examining effects of social isolation on depression-related endpoints in a nonhuman primate. The findings also suggest that trait-like differences in emotional responsiveness during separation in infancy may predict differences in responsiveness during social isolation in adulthood.